100 healthy recipes healing vegetarian recipes : delicious recipes for body and mind - Vaughan, Sarah (London Bounty Books, 2017)
This collection of 100 vegetarian recipes starts with nutritious meals for simply looking good and feeling good, including weight loss and detox recipes as well as ideas for healthy skin, eyes, muscles and joints, etc. In part two the â€˜Recovery and Recuperationâ€ recipes target common complaints such as colds, hangovers, insomnia and anaemia; while part three focuses on foods to combat stress and depression and nourish soul and spirit.--Provided by publisher.
Keywords: Vegetarian cooking; Cooking (Natural foods)